2012
DOI: 10.1155/2012/264986
|View full text |Cite
|
Sign up to set email alerts
|

AttenuatedSalmonella typhimuriumSV4089 as a Potential Carrier of Oral DNA Vaccine in Chickens

Abstract: Attenuated Salmonella has been used as a carrier for DNA vaccine. However, in vitro and in vivo studies on the bacteria following transfection of plasmid DNA were poorly studied. In this paper, eukaryotic expression plasmids encoding avian influenza virus (AIV) subtype H5N1 genes, pcDNA3.1/HA, NA, and NP, were transfected into an attenuated Salmonella enteric typhimurium SV4089. In vitro stability of the transfected plasmids into Salmonella were over 90% after 100 generations. The attenuated Salmonella were ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Recent studies have shown that live attenuated Salmonella is an effective vector for delivery of heterologous antigens or DNA to the immune system [ 17 18 23 37 ]. In addition, live vectors can mimic the natural process of Salmonella infection through the oral route, resulting in mucosal and systemic immune responses against the pathogen's antigen [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that live attenuated Salmonella is an effective vector for delivery of heterologous antigens or DNA to the immune system [ 17 18 23 37 ]. In addition, live vectors can mimic the natural process of Salmonella infection through the oral route, resulting in mucosal and systemic immune responses against the pathogen's antigen [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…DNA vaccines are inexpensive to produce in large doses and are easily detected and monitored after oral inoculations into the host. Furthermore, attenuated S. typhimurium SV4089 was able to invade and pass through the various organs of inoculated chickens, such as the liver, spleen, and caecum, without showing evidence of systemic infection [64].…”
Section: Biological Carriersmentioning
confidence: 99%
“…In this regard, Salmonella-based vaccine systems are considered among the most advanced and promising technologies developed to induce immunological protection against enteric pathogens because of their ability to both colonize the small intestine and invade non-phagocytic epithelial cells, thus allowing access to the underlying lymphoid tissue [32]. Taking advance of the use of Salmonella as live bacterial carrier, our group developed a Salmonella vaccine candidate expressing the 30-mer peptide derived from gp43 (amino acid residues 210-239, designated as Ag30) from T. spiralis ML.…”
Section: Second-generation Vaccinesmentioning
confidence: 99%